The rat Pkd2 protein assumes distinct subcellular distributions in different organs - Obermüller, Nicholas; Gallagher, Anna Rachel; Cai, Yiqiang; Gaßler, Nikolaus; Gretz, Norbert; Somlo, Stefan; Witzgall, Ralph (American journal of physiology. Renal physiology, 1999)
Mutations in thePKD2 gene account for ∼15% of all cases of autosomal-dominant polycystic kidney disease. In the present study the cellular distribution of the Pkd2 protein was investigated by immunohistochemistry in different rat organs. Although the Pkd2 protein showed a widespread expression, a strikingly different distribution of the protein was observed between individual organs. Whereas in renal distal tubules and in striated ducts of salivary glands a basal-to-basolateral distribution of Pkd2 was found, a punctate cytoplasmic location was detected in the adrenal gland, ovary, cornea, and smooth muscle cells of blood vessels. Interestingly, in the adrenal gland and ovary, the rat Pkd2 protein was more heavilyN-glycosylated than in the kidney and salivary gland. These results suggest that Pkd2 accomplishes its functions by interacting with proteins located in different cellular compartments. The extrarenal expression pattern of the Pkd2 protein hints at other candidate sites of disease manifestations in patients carryingPKD2 mutations.
Gesehen am 08.06.2022